ChemInform Abstract: Palladium‐Catalyzed Cross‐Coupling of Unactivated Aryl Sulfides with Arylzinc Reagents under Mild Conditions. Issue 14 (April 2015) - Otsuka, Shinya; Fujino, Daishi; Murakami, Kei; Yorimitsu, Hideki; Osuka, Atsuhiro
Abstract: The title coupling reaction tolerates various functional groups in both reactants.